Utilização de SIG “open souce” no ordenamento apícola. Caso de estudo: área controlada de Castelo Branco. - Roque, N. (2017)
Utilização de SIG “open souce” no ordenamento apícola. Caso de estudo: área controlada de Castelo Branco.